Recent advances in models for screening potential osteoporosis drugs. (3rd August 2018) - Merlotti, D.; Materozzi, M.; Picchioni, T.; Bianciardi, S.; Alessandri, M.; Nuti, R.; Gennari, L.
ABSTRACT: Introduction : Osteoporosis is a growing health and health-economic problem due to the increased proportion of elderly people in the population. Basic and clinical advances in research over the past two decades have led to the development of different compounds with antiresorptive or anabolic activity on bone that improved substantially the management of patients with osteoporosis over calcitonin or estrogen replacement. New compounds are in preclinical and clinical development. Areas covered : In this review, the authors review the approaches for the preclinical and clinical development of antiresorptive and anabolic agents for osteoporosis, particularly focusing on the recent advances in technology and in the understanding of skeletal biology, together with their implications on novel osteoporosis drug discovery. Expert opinion : Based on the available evidence from the approved drugs for the treatment osteoporosis as well as from the different compounds under clinical development, it has become clear that long term nonclinical pharmacological studies with either bone quality and off-target effects as the main outcomes should be required for new drugs intended to treat osteoporosis. At the same time, basic and clinical advances in research have underlined the necessity to develop new technologies and new models for a thorough screening of the effects of new drugs on the different components of skeletal aging and bone fragility that cannot be assessed by bone mass measurement.